Legal Uncertainty in the Protection of Workers’ Rights at Retirement Age: A Normative–Empirical Study Within Indonesia’s Pancasila Welfare State Framework - Torang Maruli Manalu, David; Citrawinda, Cita; Sinaga, Parbuntian; Hartanto, Hartanto; Budiman, Anwar (Ridwan Institute, 2026)
This study examines legal uncertainty concerning the protection of workers’ rights upon reaching retirement age within Indonesia’s labor law regime. The research is motivated by inconsistencies in regulatory norms, ambiguities in legal provisions, and disparities in judicial interpretations regarding retirement entitlements. Employing a normative–empirical methodology, the study analyzes statutory regulations, court decisions, and empirical data obtained from interviews with stakeholders, including labor authorities, employers, and workers. The findings reveal that legal uncertainty primarily stems from incomplete regulatory formulations in Government Regulation No. 35 of 2021, particularly regarding procedures for retirement-related termination, calculation mechanisms for retirement benefits, and the legal status of pension fund contributions. Moreover, the regulation disproportionately positions employers as the dominant party in retirement decisions, thereby generating procedural injustice and weakening workers’ bargaining power. Judicial practices further demonstrate interpretative variations that contribute to inconsistent legal outcomes. The study argues that legal reconstruction is necessary to ensure certainty, fairness, and balance in retirement-related employment termination. It proposes strengthening normative clarity, recognizing workers’ rights to initiate retirement, and enhancing tripartite synergy among government, employers, and labor unions. The research contributes to the discourse on labor protection by advancing a justice-oriented framework aligned with the principles of the Pancasila Welfare State.